Respondents' Exposure to Community‐based Services and Reported Fertility‐Regulation Behavior: A Decade of Data from the Navrongo Community Health and Family Planning Project. Issue 1 (March 2016) - Jackson, Elizabeth F.; Bawah, Ayaga A.; Williams, John E.; Phillips, James F.
Abstract : This article examines a decade of demographic surveillance data from rural northern Ghana linked with prospective panel survey data recording respondents' reported fertility‐regulation behavior. We assess the impact of access to community‐based contraceptive services, reported fertility‐regulation behavior, and their interaction on the risk of a conception that results in a birth. The effects of service exposure differ by marital status. Reported use of any method to delay or avoid pregnancy appears to be more effective in reducing the risk of conception among the unmarried in areas offering community‐based contraceptive services, relative to those in areas where services are facility based. Among both married and unmarried survey respondents who state that they are not using contraception, the risk of conception is lower among women in areas with community‐based services than among women in communities without these services. The lower risk of conception among women who are receiving community‐based services and who report that they are regulating their fertility may be due to increased efficacy and duration of fertility regulation. Among women who report that they are not regulating their fertility, under‐reporting of contraceptive use in experimental areas is likely to play a role in explaining these findings.